KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI SMP PLUS LABORATORIUM INDONESIA - Prismawinda Aniva Nutqhi; Slamet Sholeh; Khalid Ramdhani (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
Education is one of the important things in a nation to face the times. In an effort to improve the quality of educational resources, one of which is the ongoing learning process. This can be realized because of the existence of teaching staff, where teaching staff is an aspect of human resources that must be developed and fostered periodically. Successful educational institutions cannot be separated from the role of a professional leader who is able to manage the institution. The principal must be able to manage everything in the school starting from planning, implementation, to evaluation. The school principal has an important role in improving the quality of his teaching staff. Various ways to improve quality have been carried out, but there are still failures and have not produced maximum results as expected. This failure occurred due to problems in education management that were not appropriate, lack of guidance on the quality of human resources, and placement of workers who did not match their expertise. This study aims to describe the managerial competence of school principals in improving the quality of teaching staff at SMP Plus Laboratory Indonesia Karawang. This research was conducted using a qualitative descriptive method. The data sources for this research are the principal and several teaching staff. Data collection techniques in this study were carried out by observation and interviews. The data analysis technique used in this study is data reduction, data presentation and conclusions. The results obtained are 1. The managerial competency of the principal in which there are sub-discussions of planning, implementation and supervision. 2. The quality of the teaching staff.